Grammatical aspect and L2 learners’ online processing of temporarily ambiguous sentences in English: A self-paced reading study with German, Dutch and French L2 learners - Roberts, Leah; Liszka, Sarah Ann (Second language research, 2021)
The results of a self-paced reading study with advanced German, Dutch and French second language (L2) learners of English showed that their online comprehension of early closure (EC) sentences which are initially misanalysed by native English speakers (e.g. While John hunted the frightened rabbit escaped) was affected by whether or not, like English, their first language (L1) encodes aspect grammatically (French) or only via lexical means (German, Dutch). The English and the higher proficiency French participants showed a processing asymmetry in their online reading of the temporarily ambiguous sentences, assumed to be caused by the difference in the aspectual perspective a comprehender takes when initial verbs appear in the past simple vs. the past progressive. In contrast, the German and Dutch learners, irrespective of proficiency, treated both progressive and simple sentences in the same way, despite the fact that all the L2 learners were matched according to their metalinguistic knowledge of English aspectual distinctions. Furthermore, despite patterning with the German learners online, the Dutch L2 learners’ offline judgments were more akin to those of the English native speakers and the French L2 learners, showing an effect of aspect, which could be argued to lend support to the idea that progressive aspect may be becoming grammaticalized in Dutch. Taken together, the results of this study add to our growing understanding of cross-linguistic influences during online L2 sentence processing, and differences between L2 parsing and learners’ metalinguistic L2 performance.